Słownik języka Jana Chryzostoma Paska odczytany feministycznie - Sobolewska, Katarzyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The feminist interpretation of The Dictionary of the language of Jan Chryzostom Pasek consisted in searching for information on the status and position of women during the baroque period, and in tracing these lexicographic tools, which revealed the hierarchy of gender related values employed by its editors. The analysis focused on lexicographic articles describing persons of female gender in juxtaposition with their male counterparts. The Dictionary reflects all of the central features of patriarchal culture of Polish Sarmatia and the entailed asymmetry of gender roles. However, as the gender category has not been sufficiently accounted for in the lexicographic treatment of personal nouns, The Dictionary does not appreciate some of the cultural content.